A light-up probe with aggregation-induced emission characteristics (AIE) for selective imaging, naked-eye detection and photodynamic killing of Gram-positive bacteria1. Issue 62 (11th August 2015) - Feng, Guangxue; Yuan, Youyong; Fang, Hu; Zhang, Ruoyu; Xing, Bengang; Zhang, Guanxin; Zhang, Deqing; Liu, Bin
<x xml:space="preserve">Abstract</x> We report a multifunctional light-up probe based on AIEgens for selective recognition, naked-eye identification, and photodynamic killing of Gram-positive bacteria including vancomycin-resistant strains.